Analysis of the Application of Occupational Safety and Health on Tower Cranes to the Risk of Work Accidents - Nuralam, Wulan Siti; Puteri, Dea Kania; Iryani, Rinrin Dwi; Rozy, Niko (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to assess workers' compliance with Occupational Safety and Health (OSH) implementation and risk control using Hazard Identification Risk Assessment and Risk Control (HIRARC) and Job Safety Analysis (JSA) methods on tower cranes to reduce workplace accident risks. Using a quantitative descriptive method through questionnaires, interviews, and field observations, the study found that workers' compliance is generally high but still not optimal, requiring further actions such as regular monitoring, safety patrols, and preventive measures. Risk identification using HIRARC identified 21 high-risk variables and 1 medium-risk variable. Risk control was implemented through the Hierarchy of Control and JSA methods, helping reduce potential hazards and improve safety performance on tower crane operations in the workplace.